Estudo das interfaces parlay e contribui??o para um gateway parlay x aplic?vel nas NGNS - Carvalho, Rodrigo Pimenta (2008)
The technological convergence toward an IP network has been a landmark without a return that allows more flexibility, development speed, money saved, services diversification, interactivity, network access spray, besides a whole world of new opportunities. Looking at this scenario, and concerned with the invoices reduction, the telecommunications companies have fomentted the new techologies development, able to modernaize their services staffs and applications. One of the main proposals, according to this, is the exposure of the telecommunications networks services and capabilities through gateways, that implement open APIs, such as: Parlay/OSA and Parlay X. The aim is that, through those APIs, a significant amount of software developers will get together with the telecommunication industry, bringing new and creative applications. Currently, the experienced professionals in Information Technology, with the software development technologies, such as Java, XML, JSP, and Web Services complete the new companies outsourced job's environment, because they, themselves, bring knowledges, that are not in the Telecommunications professionals' domain. On the other hand, the IT professionals, seeking entering the Telecommunications market, but without having skills about the technologies from this market, need the common interfaces, which make possible the companies networks requirements' skills. Therefore, the APIs that describe the companies capabilities (and the domain about using them) are the ?bridges? between the IT and Telecommunication worlds. It is the IT/Telecom or ICT convergence. To this idea becomes true, there must be works focused on those APIs implementation, and how to become them available. That is the first focus of this work: to show how these networks and fucntionalities can be exposed properly to someone else, through Parlay Interfaces, implemented in gateways, together with the next generation converged networks. Another important focus was a methodology definition to reach this purpose. Eventually, it was explored Parlay interfaces with gateway emulation, showing and discussing the necessary technologies to their use, besides contributing.